ADAPT study: adaptation of evidence-informed complex population health interventions for implementation and/or re-evaluation in new contexts: protocol for a Delphi consensus exercise to develop guidance. Issue 7 (20th July 2020) - Campbell, Mhairi; Moore, Graham; Evans, Rhiannon E; Khodyakov, Dmitry; Craig, Peter
Abstract : Introduction: Complex population health interventions that are effective in one context may not be effective elsewhere, and may even be harmful. As such, an intervention may require adaptation to ensure it fits with a new context. To date, there is no overarching guidance to help researchers to adapt and evaluate interventions in new contexts, and no criteria to support research funders or journals assess proposed or reported adaptations or evaluation. There is limited assistance for policy-makers and practitioners to decide if evidence-informed interventions are appropriate to their context, or if adaptation and further evaluation is needed. This Delphi exercise will contribute to the development of guidance for these communities to support the adaptation, implementation and/or re-evaluation of complex population health interventions in new contexts. Methods: We will conduct a Delphi consensus exercise to gather expert opinion from researchers, research funders, journal editors and policy-makers. Expert opinion will be sought on: appropriate definitions and concepts, identifying key methodological considerations and establishing adaptations and processes to be undertaken during adaptation of complex population health interventions in new contexts. Ethics and dissemination: Ethics approval for the Delphi exercise has been obtained from the University of Glasgow and and the RAND institutional research board. Dissemination of the results of this study will be through peer-reviewed publications, workshops at national and international conferences, and a summary of the guidance developed for key organisations and stakeholders.